2021
DOI: 10.1186/s12909-021-02825-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors influencing the network teaching effect of college students in a medical school during the COVID-19 epidemic

Abstract: Background The purpose of this study is to understand the influencing factors of Chinese college students’ satisfaction with online teaching and psychological pressure on learning during the novel coronavirus epidemic. Methods We assessed the effect of online teaching of 7084 medical students from wannan medical college in March 5 to April 2, 2020 using cluster sampling. The respondents were asked to complete a 7-item self-compiled online teaching … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Students with poor information capability are prone to confusion when facing multichannel information-based teaching. Recent literature has pointed that 32.9% of Chinese college students were unfamiliar operation of the learning platform and unfamiliar learning platform operation of the students was a risk factor for psychological stress ( Yu et al, 2021 ). Another large survey in China demonstrated that students were most familiar with recorded broadcast courses (36.84%) and massive open online courses (MOOCs) (35.00%) and they considered the support and service of platforms to be insufficient ( Wang C. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Students with poor information capability are prone to confusion when facing multichannel information-based teaching. Recent literature has pointed that 32.9% of Chinese college students were unfamiliar operation of the learning platform and unfamiliar learning platform operation of the students was a risk factor for psychological stress ( Yu et al, 2021 ). Another large survey in China demonstrated that students were most familiar with recorded broadcast courses (36.84%) and massive open online courses (MOOCs) (35.00%) and they considered the support and service of platforms to be insufficient ( Wang C. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the process of learning, learning from each other can promote the progress of teaching ( Zhang et al, 2019 ). Most students cannot adapt to the fully online teaching model in a short time ( Yu et al, 2021 ). Prevention and isolation measures implemented during the COVID-19 pandemic have drastically changed the learning environment and cooperation methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with females, males may be less adaptable to online learning. According to a study, males showed higher psychological pressure during online learning ( 48 ). This survey was conducted in June, one month before the final exam for medical students.…”
Section: Discussionmentioning
confidence: 99%